Evaluation of Nutrient and Anti-Inflammatory Drugs Removal Using a Pilot-Scale Novel Hybrid Biofilm Process - Cokgor, Emine; Soylu, Dilsad; Ozyildiz, Goksin; Topuz, Emel; Zengin, Gulsum Emel; Guven, Didem; Pala-Ozkok, Ilke (Springer, 2025)
Moving bed biofilm reactor (MBBR) is a promising and cost-effective treatment technology for efficient nutrient removal. In this study, a pilot-scale novel MBBR-based hybrid biofilm system, integrating suspended and attached growth biomass, was operated to treat real domestic wastewater. The system included a reactive primary sedimentation step designed to capture particulate organic matter and redirect both sludge and effluent through distinct treatment pathways to enhance overall nutrient and micropollutant removal. The patented hybrid system was operated for 6 months, and 79, 84, and 90% removal efficiencies were achieved for chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP), respectively. Except diclofenac (32%), naproxen, ibuprofen, ketoprofen, and mefenamic acid (70%, 96%, 70% and 75%) were efficiently removed. Specifically, ketoprofen and mefenamic acid removals were markedly improved in the hybrid biofilm system compared to the full-scale conventional Biological Nutrient Removal (BNR) plant. The population dynamics were also monitored via molecular analysis on the sludge samples, differentiating the microbial community in MBBR and conventional BNR. Results showed that an abundance shift in the community structure at the species level between the two sludge structures of MBBR and conventional BNR. Acinetobacter sp. (35%) and uncultured Arcobacteraceae sp (22%) were found to be the dominant species in the hybrid system.
Keywords: Anti-inflammatory drugs; domestic wastewater; MBBR; micropollutants; population dynamics.